Effects of Collision with a Self-Propeller Oil Barge Ship on a Navigational Buoy - Wilma Amir Amiruddin; Ahmad Firdhaus; Hartono Yudo; Firmansyah Aulia Rakhman (International Journal of Marine Engineering Innovation and Research, 2023)
A navigation buoy is a navigational aid tool that is very important in supporting the safety of shipping lanes. However, navigation buoys are often lost and damaged, caused by several factors, one of which is being hit by a ship. Therefore, it is essential to conduct this research to determine the damaging effect on the navigation buoy after being hit by a vessel and to determine the effectiveness of using medium-density polyethylene material in the navigation buoy structure. This study uses a finite element numerical simulation method by making three variations of speed, as well as two variations of the angle of impact, namely 0° and 45°, which lasted for 0.1 seconds and was assisted by FEA software. The simulation results indicate that the largest maximum deformation occurs when the ship strikes the buoy with a speed of 7 m/s at an angle of 0° of 0.6 m. In this scenario, there is also a significant damage condition that results in tearing the buoy shell's surface by as many as 413 elements, or 1.24 m. The most extraordinary kinetic and internal energy produced occurred at a speed of 7 m/s with an angle of 45° of 147.15 kJ and 45.70 kJ. Therefore, it can be stated that the amount of buoy damage caused by a ship collision is dictated or impacted by the starting speed of the ship and the angle of impact state the most important part of your findings and achievements